PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP RETURN SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING DAN MODERATING (Studi Empiris Pada Perusahaan Peraih CGPI Yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2012) - ROY BUDIHARJO (Universitas Mercu Buana, 2016)
ABSTRACT The purpose of this study are as follows: 1) Finding empirical evidence about the influence of good corporate governance to profitability; 2) Finding empirical evidence of good corporate governance influence on stock returns; 3) Finding empirical evidence Profitability influence on stock returns; 4) Finding empirical evidence of good corporate governance influence on stock returns through profitability; 5) Finding the empirical evidence regarding the extent of profitability may moderate the relationship between good corporate governance with stock return. The analysis used is path analysis (path analysis, test Moderated Regression Analysis (MRA), Sobel test Test and bootstrapping. The results showed, 1) Variable good corporate governance has a negative effect on profitability; 2) Variable good corporate governance has no effect on stock returns; 3) Variable profitability as measured by return on assets (ROA) has a significant positive effect on stock returns; 4) Variable good corporate governance positively affects stock returns through profitability; 5) Variable profitability as measured by return on assets (ROA) was not shown to moderate the relationship between good corporate governance with stock return. Keywords: Good Corporate Governance, Profitabilitas, Return Saham, CGPI